Development of Islamic Interactive Multimedia Material on Energy Sources to Improve Motivation and Learning Outcomes of Class III Students of MI Islamiyah Malang City - Febrianti, Aristhalia Hevi; Susilawati, Samsul; Minarno, Eko Budi (Abjadia : International Journal of Education, 2025)
This study explores the development of Islamic interactive multimedia to enhance motivation and students learning outcomes in science classes. The media was developed using the Lee and Owens model, which consists of five systematic stages: analysis, design, development, implementation, and evaluation. The research employed a Research and Development (R&D) method, involving 20 grade 3 students of MI Islamiyah Malang City as research subjects. Data were collected through teacher interviews, classroom observations, expert validation, student motivation questionnaires, and pre- and post-tests. Findings reveal that the media significantly improves intrinsic motivation by fostering curiosity, interest, learning satisfaction, and spiritual values, as well as extrinsic motivation through immediate feedback, symbolic rewards, and progressive challenges. Learning outcomes also improved significantly from the pre-test to the post-test (p < 0.05). The integration of Islamic values, such as environmental responsibility and energy conservation inspired by the Prophet Muhammad, fosters both affective and spiritual reinforcement. The study concludes that Islamic interactive multimedia is an effective and relevant tool for creating innovative and engaging learning environment in the madrasah.